2017
DOI: 10.1534/genetics.116.196881
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionarily Conserved Role of Presenilin in Neuronal Protection in the Aging Drosophila Brain

Abstract: Mutations in the genes are the major genetic cause of Alzheimer's disease. Presenilin and Nicastrin are essential components of γ-secretase, a multi-subunit protease that cleaves Type I transmembrane proteins. Genetic studies in mice previously demonstrated that conditional inactivation of Presenilin or Nicastrin in excitatory neurons of the postnatal forebrain results in memory deficits, synaptic impairment, and age-dependent neurodegeneration. The roles of () and () in the adult fly brain, however, are unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…The presenilin hypothesis, which posits that PSEN mutations cause FAD via a loss of essential presenilin functions in the brain, was prompted by the age-dependent cortical neurodegeneration and dementia observed in Psen conditional double-knockout mice (3)(4)(5), along with the lack of neurodegeneration reported in transgenic mice overexpressing PSEN1 mutations (6, 7). The hypothesis was further supported subsequently by genetic findings in the Drosophila and mouse brain showing that partial loss of PS function also results in age-dependent neurodegeneration (8,9), and by studies in cultured cells and knock-in mouse brains demonstrating that PSEN1 mutations cause loss of γ-secretase activity and impair essential PS functions in learning and memory, synaptic function, and neuronal survival (10)(11)(12)(13). The findings from these mammalian studies are consistent with genetic data obtained in Caenorhabditis elegans and Drosophila showing that relative to wildtype PS1, mutant PS1 exhibited reduced biological activities (14,15).…”
mentioning
confidence: 87%
“…The presenilin hypothesis, which posits that PSEN mutations cause FAD via a loss of essential presenilin functions in the brain, was prompted by the age-dependent cortical neurodegeneration and dementia observed in Psen conditional double-knockout mice (3)(4)(5), along with the lack of neurodegeneration reported in transgenic mice overexpressing PSEN1 mutations (6, 7). The hypothesis was further supported subsequently by genetic findings in the Drosophila and mouse brain showing that partial loss of PS function also results in age-dependent neurodegeneration (8,9), and by studies in cultured cells and knock-in mouse brains demonstrating that PSEN1 mutations cause loss of γ-secretase activity and impair essential PS functions in learning and memory, synaptic function, and neuronal survival (10)(11)(12)(13). The findings from these mammalian studies are consistent with genetic data obtained in Caenorhabditis elegans and Drosophila showing that relative to wildtype PS1, mutant PS1 exhibited reduced biological activities (14,15).…”
mentioning
confidence: 87%
“…However, neuronal knockdown of Presenilin or other γ-secretase complex subunits such as Nicastrin revealed that γ-secretase activity is essential for neuronal maintenance. These flies exhibited shortened life-span and age-dependent climbing defects accompanied by histological signs of neurodegeneration (Kang et al, 2017). Interestingly, brain specific knockout of Psen1 , Psen2 or Nicastrin in mice also results in neurodegenerative features independent of β-amyloid accumulation (Beglopoulos et al, 2004; Feng et al, 2004; Saura et al, 2004; Tabuchi et al, 2009), pointing to an evolutionarily conserved function of the γ-secretase complex in neuronal maintenance.…”
Section: Contributions Of Drosophila To Neurodegeneration Researchmentioning
confidence: 99%
“…Previous genetic studies demonstrated that selective inactivation of PS in excitatory neurons of the cerebral cortex results in age-dependent, progressive neurodegeneration including increases of apoptosis and gliosis [ 11 13 , 16 ]. Subsequent studies further showed that partial reduction of PS expression in excitatory neurons of the mouse cerebral cortex or in neurons of the Drosophila brain also causes age-dependent neurodegeneration and increases of apoptosis [ 17 , 43 ]. In this study, we continue this reductionist approach to dissect the role of PS in inhibitory interneurons of the cerebral cortex through the generation and analysis of IN- PS cDKO mice, in which PS expression is selectively inactivated in inhibitory interneurons using GAD2-IRES-Cre , which was shown previously to drive Cre-mediated recombination in > 90% cortical interneurons [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, no neuronal loss was observed in the cerebral cortex of Notch1/2 cDKO mice [ 58 ] and APP/APLP1/APLP2 conditional triple knockout mice [ 59 ], demonstrating that PS mediated cortical neuronal survival is not regulated through the Notch or APP family. Given the fact at any given time only 0.1–0.2% of excitatory or inhibitory cortical neurons lacking PS undergo apoptosis, making it impossible to perform biochemical analysis to gain insight into the molecular mechanism, we have therefore developed Drosophila models [ 43 ] and are now looking for genes that modulate age-dependent neurodegeneration caused by partial loss of Psn, the Drosophila homolog of Presenilin .…”
Section: Discussionmentioning
confidence: 99%